The role of sexual abuse on functional neuroimaging markers associated with major depressive disorder. (3rd October 2015) - Skokauskas, Norbert; Carballedo, Angela; Fagan, Andrew; Frodl, Thomas
Abstract : Objectives. Victims of child sexual abuse can develop depression and other mental health conditions that follow them well into adulthood. This study aimed to clarify the role of sexual abuse (SA) on functional imaging markers associated with MDD. Methods. Thirty-seven patients with MDD only; and 13 patients with both MDD and SA and 43 healthy controls performed emotional attention shifting tasks during fMRI session. Clinical diagnoses were made by consultant psychiatrists based on the DSM-IV-TR criteria and diagnoses were confirmed using SCID-I. Magnetic resonance images were obtained with a Philips Achieva 3 Tesla MRI scanner. Short form childhood trauma questionnaire, Hamilton Rating Scale for Depression and Beck's Depression Inventory were also employed. Data were analysed with Statistical Parametric Mapping 8 (SPM8). Results. Using the contrast judgment of emotion minus judgment of geometry following emotional neutral stimuli, patients with MDD showed significantly reduced activation in comparison to healthy controls in the area of the right fusiform gyrus. With the contrast judgment of emotion minus judgment of geometry following emotional negative stimuli, participants with MDD and SA showed significantly higher activation in the area of the left inferior parietal lobe in comparison to participants with MDD without SA. Conclusions. The history of sexual abuse affects functional neuroimaging markers associated with major depressive disorder.